PERAN NEGARA DALAM MENJAMIN HAK BEBAS DARI KELAPARAN - Kusuma Wardhana, Tri Aji Nur Dewa; Afifah, Wiwik; Fikri, Sultoni (IBLAM LAW REVIEW, 2022)
Indonesia is a developing country that has a very large population, in this case, the natural resources in Indonesia must be utilized efficiently so that all citizens get the results evenly. must guarantee the right to freedom of citizens from hunger which is one of the basic needs in human rights whose fulfillment is guaranteed by law and international conventions on economic, social, and cultural rights. For this reason, the state's right to food must be fulfilled as a means of fulfilling food needs. Broadly speaking, the fulfillment of the right to food is still experiencing various problems in various aspects. Such as reduced agricultural land and decreased productivity due to climate change. This study aims to determine the role of the government in supporting the guarantee of the right to be free from hunger which is the basis of human rights. This research method is a qualitative method based on existing data on the fulfillment of the right to be free from hunger. The government is responsible for food availability through regional food security to support national food security based on the principles of sovereignty and independence. For this reason, a policy for the protection and conservation of agricultural land is needed, as well as a strong commitment and goodwill of the local government to prioritize the development of local food security.